2022
DOI: 10.1108/imds-12-2020-0727
|View full text |Cite
|
Sign up to set email alerts
|

Value drivers of government issued mobile coupons usage

Abstract: PurposeIn the pandemic time, many local governments in China issue mobile coupons to citizens in order to boost economy via stimulating consumption. This study examines value drivers for consumers to use government issued mobile coupons (GIMCs), which differ from traditional ones issued by retailers, during the pandemic time in mainland China.Design/methodology/approachContent analysis of 148 posts and 388 comments from Sina Weibo were performed to identify value-related antecedents of GIMCs' usage by consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…[3] sought to understand the role of social networking sites in the development of tourism in Al-Kharj Governorate, and the study concluded that these sites have a role in persuading tourists to visit the governorate. As for the study by [19], it found that the research on functional value (driven by economic benefits, convenience, and relevance), emotional value (driven by trustworthiness, competition, and altruism), and social value. A study [13] concluded the importance of using mobile applications in motivating customers to use the company's products.…”
Section: Literature Reviewmentioning
confidence: 86%
“…[3] sought to understand the role of social networking sites in the development of tourism in Al-Kharj Governorate, and the study concluded that these sites have a role in persuading tourists to visit the governorate. As for the study by [19], it found that the research on functional value (driven by economic benefits, convenience, and relevance), emotional value (driven by trustworthiness, competition, and altruism), and social value. A study [13] concluded the importance of using mobile applications in motivating customers to use the company's products.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Some e-business scholars have confirmed the significance of social value in online and offline purchases (e.g., Wu et al, 2018 ; Yu and Huang, 2022 ). During the COVID-19 situation, social benefits from interpersonal communications could improve the social connection between consumers and other people, generating a better customer experience and intention to purchase ( Zhang and Zhang, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dining in a restaurant involves considerable social value for consumers ( Park, 2004 ), which cannot be ignored, especially in the context of COVID-19, which involves social distancing practices ( Lim et al, 2022 ; Mahmood et al, 2022 ). However, recent literature has not studied hedonic, utilitarian, and social values simultaneously ( Kakar, 2020 ) in the context of COVID-19 ( Zhang and Zhang, 2022 ), which warrants further studies.…”
Section: Literature Reviewmentioning
confidence: 99%